Systemic risk and financial development in a monetary model - Philippe Moutot (European Central Bank (ECB), 2011)
In a stochastic pure endowment economy with money but no financial markets, two types of agents trade one non-durable good using two alternative types of cash constraints. Simulations of the corresponding variants are compared to Arrow-Debreu and Autarky equilibriums. First, this illustrates how financial innovation or financial regression, including systemic risk, may arise in a neo-classical model with rational expectations and may or may not be countered. Second, the price and money partition dynamics that the two variants generate absent any macroeconomic shock, exhibit jumps as well as fat-tails and vary depending on the discount rate.
Keywords: E44; 330; Cash constraints; Financial Development; heterogeneity; monetary model; Rational Expectations; systemic risk